2019
DOI: 10.1149/2.0051913jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Analysis of Symmetrical Ni/Gadolinium-Doped Ceria (CGO10) Electrodes in Electrolyte-Supported Solid Oxide Cells

Abstract: One of the most powerful tools in solid oxide cell (SOC) characterization is electrochemical impedance spectroscopy, which can unfold important insights into SOC performance characteristics and degradation behavior. To obtain a better understanding of the electrochemical behavior of Ni/CGO fuel electrodes, this work presents a comprehensive investigation of state-of-the-art Ni/CGO10based electrolyte-supported cells. Commercial Ni/CGO10|CGO10|3YSZ|CGO10|Ni/CGO10 symmetrical cells were characterized between 550-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 40 publications
10
84
1
Order By: Relevance
“…Moreover, for Ni/CGO-based cells of the same type as used in the present study, we have reported the peak frequency of the anode charge transfer process to be between 1-10 Hz. [18,23] The impedance response at these frequencies is also increased in comparison with the cells with 25 μm thick L65SCrN and 19 μm thick L70SCrN anodes and responsible for the difference in polarization resistance between the cells. The increased polarization resistance of the cell with 8 μm thick L65SCrN electrode is mainly caused by an increased impedance response at frequencies of approximately 1 Hz.…”
Section: Electrochemical Performancementioning
confidence: 98%
“…Moreover, for Ni/CGO-based cells of the same type as used in the present study, we have reported the peak frequency of the anode charge transfer process to be between 1-10 Hz. [18,23] The impedance response at these frequencies is also increased in comparison with the cells with 25 μm thick L65SCrN and 19 μm thick L70SCrN anodes and responsible for the difference in polarization resistance between the cells. The increased polarization resistance of the cell with 8 μm thick L65SCrN electrode is mainly caused by an increased impedance response at frequencies of approximately 1 Hz.…”
Section: Electrochemical Performancementioning
confidence: 98%
“…Before performing a quantitative analysis, the peak resistances need to be corrected. As shown in previous modeling studies [33][34][35] and experimental studies for symmetrical cells [36,37], the low frequency polarization resistance is increased by a gas diffusion and gas conversion resistance, even for open circuit measurements. The sum of both resistances is also named gas concentration resistance R gas [38].…”
Section: Evaluation Of the Polarization Resistancementioning
confidence: 61%
“…The gas concentration resistance and its main origin (conversion or diffusion resistance in the gas channel) depend especially on the measurement setup and the gas supply. Unfortunately, R gas cannot be separated by a single peak in the DRT due to an overlapped electrode process for Ni/CGO electrodes [37]. A possible approach to approximate R gas would be the characterization of a cell with a Ni/YSZ fuel electrode, which has no characteristic overlapping process at the relevant relaxation frequency.…”
Section: Evaluation Of the Polarization Resistancementioning
confidence: 99%
“…To further evaluate the influence of the sintering temperature on the electrode performances, distribution of relaxation times (DRT) analyses of their spectra were performed. DRT analysis is a powerful tool to investigate electrochemical processes [53][54][55][56]. The results of the DRT analysis of the spectra shown in Fig.…”
Section: Electrochemical Characterisationmentioning
confidence: 99%